2014
DOI: 10.1371/journal.pone.0110793
|View full text |Cite
|
Sign up to set email alerts
|

Lombards on the Move – An Integrative Study of the Migration Period Cemetery at Szólád, Hungary

Abstract: In 2005 to 2007 45 skeletons of adults and subadults were excavated at the Lombard period cemetery at Szólád (6th century A.D.), Hungary. Embedded into the well-recorded historical context, the article presents the results obtained by an integrative investigation including anthropological, molecular genetic and isotopic (δ15N, δ13C, 87Sr/86Sr) analyses. Skeletal stress markers as well as traces of interpersonal violence were found to occur frequently. The mitochondrial DNA profiles revealed a heterogeneous spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 55 publications
2
70
0
6
Order By: Relevance
“…Six male individuals in this kindred were buried with weapons, despite three (SZ7, SZ14, SZ15) being teenagers at the time of death (12-17 yo.). The adult males in this kindred (SZ24, SZ13 and SZ22) appear to have had access to a diet particularly high in animal protein, as inferred from nitrogen isotope analysis 13 . Individual SZ13 has the deepest grave and is the only individual in the whole cemetery whose burial includes a weighing scale and a horse, which may be an indication of his differentiated status in that society.…”
Section: Both Cemeteries Are Organized Around Close Biological Relatementioning
confidence: 93%
See 2 more Smart Citations
“…Six male individuals in this kindred were buried with weapons, despite three (SZ7, SZ14, SZ15) being teenagers at the time of death (12-17 yo.). The adult males in this kindred (SZ24, SZ13 and SZ22) appear to have had access to a diet particularly high in animal protein, as inferred from nitrogen isotope analysis 13 . Individual SZ13 has the deepest grave and is the only individual in the whole cemetery whose burial includes a weighing scale and a horse, which may be an indication of his differentiated status in that society.…”
Section: Both Cemeteries Are Organized Around Close Biological Relatementioning
confidence: 93%
“…There are 45 graves ( Fig 1B), all of which are dated to the middle third of the sixth century based on a combination of stylistic elements of the grave goods and radiocarbon analysis 13 . Archaeological, stable isotope and mtDNA (HVS-1) analyses suggested that Szólád was occupied for only~20/30 years by a mobile group of "Longobard era" settlers 13 . The female to male ratio (sexing being based primarily on genetic data, or in its absence, anatomy) is 0.65.…”
Section: Two Longobard-associated Cemeteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lombards for e.g., who directly preceded the Avars in Transdanubia (today's Western Hungary), migrated across the Carpathian Basin to Italy in the mid-6 th century. The population of two analysed Lombard cemeteries in Hungary and Italy showed the Central and North European genomic ancestry of this Germanic tribe 18,19 .…”
Section: Background Of the Bioarchaeological Researchmentioning
confidence: 96%
“…The only ancient genetic data ever published from cemeteries associated with Longobard culture so far were sequences of the mtDNA control region from Piedmont, Italy 5,6 , and sequences of mtDNA control region and of informative positions in the coding region from the cemetery of Szólád in Hungary 7 . A broader analysis, based on larger assemblages of samples and genetic markers, is clearly necessary to provide a finer resolution of medieval populations movements and interactions in Europe.…”
Section: Introductionmentioning
confidence: 99%